(1169) full description of a convex polyhedron وصف كامل للمجسم المحدب - omar, amani (the institute of national planning, 2018)
programming problem have first arisen in the economics where optimal allocation of scarce resources has long been of interest to-economists. the optimal allocation problem is one of the oldest problem in formal economic theory; welfare economics, inter industry models.